An Analysis of Online Model Learning in Educational Seminar Courses at IKIP Budi Utomo - Hermina Noviana Hoar; Novi Eko Prasetyo; Titik Purwati; Deni Nugroho Setyabudi (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2021)
Corona virus (covid) has disrupted the learning process directly. So the government has issued regulations to maintain distance and social distancing. So a solution is needed to answer this problem. Online learning is one way to solve this problem. The objectives of this study are 1) To determine the implementation of the application of online learning models in educational seminar courses. 2) To find out what obstacles are the problems in the online model learning process in seminar courses. 3) To find out the development of online learning in educational seminar courses. 4) to find out the skill aspect in online model learning in educational seminar courses at IKIP Budi Utomo Malang. The research subjects are lecturers of educational seminar subjects and students of the 2018 economic education study program class A and B IKIP Budi Utomo Malang. This research is a qualitative research with descriptive analysis technique. Analysis of research data obtained from the process of searching and compiling systematically, data obtained from observations, interviews and the field, namely data collection, data reduction, data presentation, conclusions and verification. The results of the study show that (1) the implementation of the application of online model learning in the educator seminar course has been effective; (2) the obstacles that become problems in the online learning process in educational seminar courses are the internet network, communication between lecturers and students, lack of effectiveness and time efficiency, lack of enthusiasm of students in understanding the material; (3) students are able to make proposals and journals and then able to carry out educational seminars online.